2014
DOI: 10.1039/c4bm00174e
|View full text |Cite
|
Sign up to set email alerts
|

Cyclen-based cationic lipids with double hydrophobic tails for efficient gene delivery

Abstract: The gene transfection abilities and structure–activity relationship of newly designed cationic lipids were studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Other groups have reported the electrostatic interaction when the GCL contains an oligo-oxyethylene spacer [93,115], and/or other headgroups as imidazolium or pyridinium [45, 57-59, 75, 99, 116]. Looking for more biocompatible vectors, GCLs that incorporate aminoacid rests, such as GCL-lysine 12 based and GCL-arginine based [60,62,64], GCL-cholesterol based [117][118][119], and GCL-cyclen-based [120] have been also investigated. Lipoplexes containing a MVCL with dendritic-type headgroup have been also analyzed [67,121,122].…”
Section: Electrostatic Interactionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other groups have reported the electrostatic interaction when the GCL contains an oligo-oxyethylene spacer [93,115], and/or other headgroups as imidazolium or pyridinium [45, 57-59, 75, 99, 116]. Looking for more biocompatible vectors, GCLs that incorporate aminoacid rests, such as GCL-lysine 12 based and GCL-arginine based [60,62,64], GCL-cholesterol based [117][118][119], and GCL-cyclen-based [120] have been also investigated. Lipoplexes containing a MVCL with dendritic-type headgroup have been also analyzed [67,121,122].…”
Section: Electrostatic Interactionmentioning
confidence: 98%
“…TEM and/or cryo-TEM studies have reported many micrographs to characterize the size, shape, and morphology of a wide variety of lipoplexes as: (a) pDNA with GCLs [45,54,57,62,64,75,93,115,117,118,120], MVCLs [63], cationic polymers [107,133,[169][170][171] or polycations [40,84,100,136]; and (b) siRNA with cationic polymers [90,104]. Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…17 In our previous studies, we have demonstrated the potential of cyclen-based gene delivery systems. 11,12,16 On the other hand, lipids with monounsaturated hydrophobic chain(s) (e.g., oleyl group) might facilitate the transfection, since they could facilitate membrane disruption and DNA escape from endosome by increasing the membrane fluidity. 8 Many oleyl-contained lipids have been proved to be efficient delivery materials, 8,12 and some commercially available transfection reagents also have oleyl moiety in their structures.…”
Section: Introductionmentioning
confidence: 99%
“…3 Since Felgner and co-workers in 1987 first reported cationic lipid DOTMA for gene delivery, 5 an upsurge of global interest has been witnessed in the design and synthesis of novel efficient cationic transfection lipids. 6 A number of structure-activity relationship studies have demonstrated that each building block of the lipids, including positive charged polar head group, 7 hydrophobic tails, [8][9][10][11][12] linking group, [13][14][15][16] would largely influence the TEs of the delivery materials.…”
Section: Introductionmentioning
confidence: 99%